Strategy of Cash Waqf Development on Gerakan Wakaf Produktif at Baitulmaal Munzalan Indonesia Foundations in Digital Era - Bustami Bustami; Muhammad Lutfi Hakim (IAIN Ponorogo, 2020)
Abstract: The Ministry of Religion of the Republic of Indonesia released data that stated that almost 95% of waqf assets had not been used optimally. One reason is that there are only a few waqf management institutions that manage waqf property professionally and productively. Baitulmaal Munzalan Indonesia Foundation is present as one of the institutions engaged in zakat, infāq, alms, and waqf, as well as collaborating for the economic empowerment of the people. Having only been established for two years, BMI was entrusted with managing cash waqf amounting to Rp. 2,993,050,577.64 and has been distributed in the amount of Rp. 535,414,900.00 in 2018. This paper uses the type of field research and data collection techniques through interviews, documentation, and Focus Group Discussion (FGD). There are three research results in this paper. First, the Gerakan Wakaf Produktif in BMI consists of five programs, namely cash waqf, waqf asset waqf, profession waqf, benefit waqf, and waqf transfer of rights. Second, the management of cash waqf by BMI starts from planning the waqf-based infrastructure, determining the number of funds needed, and campaigning for it. The cash waqf funds collected are then used to buy raw materials used to build waqf based infrastructure. Third, BMI uses information technology in three ways, starting with collecting and managing cash waqf and its accountability report. The information technology it uses is social media, websites, and contact persons via mobile phones. الملخص: أصدرت وزارة الدين الإندونيسية بيانات تفيد بأن ما يقرب من ۹۵ في المئة من أصول الوقف لم تستخدم بالشكل الأمثل. أحد الأسباب هو أنه لا يوجد سوى عدد قليل من مؤسسات إدارة الوقف التي تدير ممتلكات الوقف بطريقة مهنية ومنتجة. تتواجد مؤسسة بيت المال منزلا إندونيسيا باعتبارها واحدة من المؤسسات العاملة في مجال الزكاة والإنفاق والصدقات والأوقاف، بالإضافة إلى التعاون من أجل التمكين الاقتصادي للناس. بعد أن تم تأسيسها لمدة عامين فقط، تم تكليف بيت المال منزلا إندونيسيا بإدارة الوقف النقدي بمبلغ ٢.٩٩٣.٠٥٠.٥٧٧,٦٤ روبية وقد تم توزيعها بمبلغ ٥٣٥.٤١٤.٩٠٠,٠٠ روبية في ٢٠١٨. تستخدم هذه الورقة نوع البحث الميداني وتقنيات جمع البيانات من خلال المقابلات والتوثيق و مناقشة جماعية فى موضوع محدد. هناك ثلاث نتائج بحث في هذه الورقة. أولاً، تتكون حركة الأوقاف الإنتاجية في بيت المال منزلا إندونيسيا من خمسة برامج، هي الوقف النقدي، والأوقاف الأصولية، والأوقاف المهنية، والأوقاف، وحقوق التحويل. ثانيًا، تبدأ إدارة الوقف النقدي من قبل بيت المال منزلا إندونيسيا من تخطيط البنية التحتية القائمة على الوقف، وتحديد مقدار الأموال اللازمة، والحملة من أجله. ثم يتم استخدام أموال الوقف النقدية التي تم جمعها لشراء المواد الخام المستخدمة لبناء البنية التحتية القائمة على الوقف. ثالثًا، يستخدم مؤشر كتلة الجسم تقنية المعلومات بثلاث طرق، بدءًا بجمع وإدارة الوقف النقدي وتقرير المساءلة الخاص به. تكنولوجيا المعلومات التي تستخدمها هي وسائل التواصل الاجتماعي والمواقع الإلكترونية وأشخاص الاتصال عبر الهواتف المحمولة. Abstrak: Kementerian Agama RI merilis data yang menyatakan bahwa hampir 95% aset wakaf belum dimanfaatkan secara optimal. Salah satu penyebabnya adalah masih sedikit lembaga pengelola wakaf yang mengelola harta benda wakaf secara profesional dan produktif. Yayasan Baitulmaal Munzalan Indonesia hadir sebagai salah satu lembaga yang bergerak di zakat, infak, sedekah, dan wakaf, serta mengkolaborasikannya untuk pemberdayaan ekonomi umat. Baru berdiri selama dua tahun, BMI dipercaya untuk mengelolah wakaf tunai sebesar Rp. 2.993.050.577,64 dan telah didistribusikan sebesar Rp. 535.414.900,00 pada 2018. Tulisan ini menggunakan jenis penelitian lapangan dan teknik pengumpulan data melalui wawancara, dokumentasi dan FGD. Ada tiga hasil penelitian dalam tulisan ini. Pertama, Gerakan Wakaf Produktif di BMI terdiri dari lima program, yaitu wakaf tunai, wakaf aset, wakaf profesi, wakaf manfaat, dan wakaf pengalihan hak. Kedua, pengelolaan wakaf tunai oleh BMI dimulai dari merencanakan infrastruktur berbasis wakaf, menetapkan jumlah dana yang dibutuhkan, dan mengkampanyekannya. Dana wakaf tunai yang terkumpul, kemudian digunakan untuk membeli bahan-bahan baku yang digunakan untuk membangun infrastruktur berbasis wakaf. Ketiga, BMI menggunakan teknologi informasi dalam tiga hal, mulai dari penghimpunan dan pengelolaan wakaf tunai serta laporan pertanggungjawabannya. Teknologi informasi yang digunakannya adalah media sosial, website dan contak person melalui handphone.